Hydrophobic to superhydrophilic tuning of multifunctional sporopollenin for microcapsule and bio-composite applications. (March 2020) - Tan, Ee-Lin; Potroz, Michael G.; Ferracci, Gaia; Wang, Lili; Jackman, Joshua A.; Cho, Nam-Joon
Graphical abstract: Abstract: Sporopollenin sporoderm microcapsules (S-SMCs) are readily extracted from plant pollen grains and provide a renewable, biocompatible source of robust microparticles for a wide range of potential applications. While the lipidic/aromatic sporopollenin copolymer surface results in a predominantly hydrophobic interface, herein, we demonstrate how ultraviolet/ozone (UV-O) light-induced tuning of S-SMC interfacial properties enables production of hydrophobic to superhydrophilic microparticles, along with programmable function for colloidal science and cellular applications. In oil/water systems, stable Pickering emulsions are achieved using S-SMCs with short duration UV-O treatment, while incorporation of superhydrophilic S-SMCs into oil/water systems provides a novel means to produce, and isolate, fully oil-loaded microparticles. Furthermore, it is shown that human cells adhere to S-SMCs acting as tissue seeds, with the controllable formation of either 3D cell spheroids or network structures. Collectively, our findings demonstrate that light-induced modification of S-SMCs has broad implications across colloidal science, microencapsulation, drug delivery, and cellular applications.